Revitalisasi dan Digitalisasi Warisan Budaya Seni Tari Tradisional Melalui Platform Edukasi Digital Sebagai Upaya Pelestarian bagi Generasi Z - Karna Aryadana; Artha Yuda (Journal of Community Development and Empowerment, 2026)
Traditional dance art is an integral part of Indonesia's cultural heritage, which currently faces the threat of extinction due to the rapid wave of globalization and shifting interests among the younger generation. This study aims to design and analyze the effectiveness of a revitalization and digitalization program for traditional dance art through the development of a digital education platform as an interactive preservation strategy for Generation Z. The research method employed is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection was conducted through questionnaires, in-depth interviews with cultural experts, and user testing involving 150 Generation Z teenagers. The results indicate that the digitalization of traditional dance materials through interactive video tutorials, Augmented Reality (AR) technology, and gamification features managed to increase participants' cultural understanding and retention by 85%. This digital education platform successfully bridged the accessibility gap and transformed the outdated perception of traditional art into a modern, flexible, and engaging learning medium. Active engagement of Generation Z in the digital space proved to foster a strong sense of belonging toward local culture. In conclusion, the synergy between the noble values of cultural heritage and digital technological innovation serves as the primary key to ensuring the sustainability of tradition in the modern era. Future research recommendations include expanding the coverage of regional dance types and integrating artificial intelligence to personalize the learning experience.